Effect of cellulose nanocrystals on crystallization kinetics of polycaprolactone as probed by Rheo-Raman. (26th September 2018) - Roy, Debjani; Kotula, Anthony P.; Natarajan, Bharath; Gilman, Jeffrey W.; Fox, Douglas M.; Migler, Kalman B.
Abstract: The development of biocompatible polymer nano-composites that enhance mechanical properties while maintaining thermoplastic processability is a longstanding goal in sustainable materials. When the matrix is semi-crystalline, the nanoparticles may induce significant changes to crystallization kinetics and morphology due to their ability to act as nucleating agents. To fully model this behavior in a process line, an understanding of the relationship between crystallinity and modulus is required. Here, we introduce a scalable model system consisting of surface-compatibilized cellulose nanocrystals (CNC) dispersed into poly(ε-caprolactone) (PCL) and study the effects of nanoparticle concentration on isothermal crystallization kinetics. The dispersion is accomplished by exchange of the Na + of sulfated cellulose nanocrystals by tetra-butyl ammonium cations (Bu4 N + ) followed by melt mixing via twin-screw extrusion. Crystallization kinetics are measured through the recently developed rheo-Raman instrument which extracts the relationship between the growth of the transient mechanical modulus and that of crystallinity. With extrusion and increasing CNC content, we find the expected enhancement of crystallization rate, but we moreover find a significant change in the relative kinetics of increase in modulus versus crystallinity. We analyze this via generalized effective medium theory which allows computation of a critical percolation threshold ξ c and discuss the results in terms of a change in nucleation density and a change in the anisotropy of crystallization. Graphical abstract: Image 1 Highlights: Rheo-Raman captures growth of modulus and crystallinity during crystallization. CNCs strongly increase crystallization kinetics of PCL. CNCs decrease percolation threshold and induces anisotropic crystalline structures.